The potential of thiosulfinates in garlic extract as urease Bioinhibitor - Ramli, N.K. (Trans Tech Publications Ltd, 2014)
Research on garlic or scientifically called as Allium sativum L. has been conducted to ensure its inhibitory effects as potentially safe and biodegradable inhibitor. From previous research, thiosulfinates (TS) contained in garlic extract proved to inhibit platelets aggregation in medical applications. TS are obtained by extracting garlic cloves. In this study, the inhibitory effect is determined by analyzing ammonia (NH3) concentration in enzyme-containing solution and standard urea assay mixtures using UV-Vis spectrophotometer device. The Beerâs law is used to calculate the concentration with an aid of the curve value of standard NH3 calibration graph. Based on previous research, the NH3 concentration is predicted to decrease with amount of enzymecontaining solution and incubation time. Â© 2014 Trans Tech Publications, Switzerland.